Keripik Daun Mangrove dalam Upaya OptimalisasiPemanfaatan Tanaman Mangrove - Desi Ramadhani; Dina Siti Maisyaroh; Cahyani Setianingrum; Dwi Retnaningsih (Idea Pengabdian Masyarakat, 2022)
Demak is an area heavily farmed with mangrove plants because part of its area is a coastal area. However, with the large number of mangrove plants in the area it has not been utilized much. Community service activities carried out from October 2021 to February 2022, we are trying to create new innovations to optimize the use of mangrove plants in the form of chips from mangrove leaves of the brayo type which we named "KRIPIROVE". By making mangrove leaves as chips, it is possible to increase the economical value of mangrove leaves, making mangrove leaf chips a healthy, inexpensive and durable snack product. Mangrove leaves have flavonoid nutritional content that can be useful as body antioxidants. The purpose of this program is to 1) Present a healthy and nutritious new diet for the community, 2) Introduce processed products of mangrove leaves that have high antioxidant nutritional content to the community that certainly has benefits for the body, 3) Create a business field for students. Implementation of manufacturing of brayo leaf chips includes: 1) Environmental observation, 2) Manufacturing planning efforts, 3) Business preparation, 4) Production stages, 5) Packaging, 6) Licensing, 7) Marketing. At first we had a hard time establishing cooperation with stall owners, so we took an alternative to delivering chip testers to drop in, when the results were satisfactory, they were willing to become partners. In addition, we market this product through online.